Drug Reaction with Eosinophilia and Systemic Symptoms (DReSS) Syndrome Associated with Liver Injury in Patient with Spondylarthritis: A Case Report - Fitri, Eyleny Meisyah; Lubis, Fatmah Azzuhra (Jurnal Kedokteran Meditek, 2025)
Introduction: Drug reaction with eosinophilia and systemic symptoms syndrome or DReSS is a rare and life-threatening severe hypersensitivity reaction characterized by multiorgan involvement, with the liver as the common visceral manifestation. Approximately 10% of patients showed no changes in their eosinophil count. Sulfasalazine and non-steroidal anti-inflammatory drugs are frequently associated with DReSS. The diagnosis of this syndrome remains challenging due to the variety of clinical presentations. Case Illustration: We reported a 48-year-old woman who presented with pruritic generalized morbilliform eruption accompanied by facial edema and fever. Five weeks prior, she was treated with sulfasalazine and diclofenac sodium for spondyloarthritis. Her laboratory results showed elevated liver, suggesting drug-induced liver injury. DReSS syndrome was diagnosed by applying the European RegiSCAR. A favorable outcome and recovery of liver function are significantly seen after withdrawal of the suspected drugs, supportive treatment, and administration of systemic corticosteroid. Discussion: Sulfasalazine was one of the drugs frequently reported to cause DReSS syndrome. Liver involvement ranges from reversible elevation of liver function tests to hepatic necrosis. Withdrawal of causative drugs and administration of methylprednisolone were recommended, particularly for DReSS with liver involvement. Conclusions: DReSS syndrome can manifest with typical skin lesions and multiorgan involvement despite the absence of eosinophilia. The leading cause of mortality related to acute liver injury ranges from mild transaminase to acute liver failure. Prompt cessation of the culprit drug, immunosuppressive therapy, and a multidisciplinary approach might prevent further complications and mortality.